PENGARUH REPUTASI KAP, KOMITE AUDIT, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AUDIT DELAY PERUSAHAAN MANUFAKTUR - Sholihah, Maulidatus; Afiqoh, Nyimas Wardatul (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study is motivated by the occurrence of audit delays in manufacturing companies during the 20192023 period, influenced by several factors, including the reputation of the public accounting firm (KAP), the presence of an audit committee, and institutional ownership. The purpose of this study is to analyze the effects of KAP reputation, audit committee, and institutional ownership on audit delays in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. A quantitative method was employed. The population consisted of manufacturing companies in the food and beverage sub-sector listed on the IDX during that period, totaling 43 companies. A purposive sampling technique was used based on specific criteria, resulting in a final sample of 36 companies. Data analysis techniques included instrument testing, classical assumption testing, and hypothesis testing. SPSS software was used as the analytical tool. The results indicate that KAP reputation, audit committee, and institutional ownership each have a negative and significant effect on audit delay.